A quality-of-life mapping function developed from a grass pollen sublingual immunotherapy trial to a tree pollen sublingual immunotherapy trial. (2nd January 2020) - Dick, Katherine; Briggs, Andrew; Ohsfeldt, Robert; Sydendal Grand, Tobias; Buchs, Sarah
Abstract: Aims: Allergic rhinitis is caused by sensitivity to environmental allergens that can significantly impact quality-of-life. The objective of this analysis was to estimate health state utilities and quality-adjusted life days (QALDs) for a tree allergy immunotherapy trial, TT-04 (EudraCT No.2015-004821-15). Health-state utilities are a measure of patient preference for health states and are necessary to derive QALDs for cost-utility analysis. Preference-based utilities were not collected in the TT-04 trial, so a mapping algorithm was developed based on a similar grass allergy immunotherapy trial, GT-08 (EudraCT No. 2004-000083-27), to estimate utilities. Methods: A two-part model was developed to predict utilities for the GT-08 trial and applied to the TT-04 trial to estimate the difference in mean utility and QALDs between SQ tree sublingual immunotherapy (SLIT)-tablet and placebo. Results: Mean utility difference between SQ tree SLIT-tablet and placebo was 0.030 [95% CI = 0.015–0.046] during the birch pollen season (BPS), 0.019 [95% CI = 0.007–0.030] during the tree pollen season (TPS) and 0.018 [95% CI = 0.007–0.030] during the full trial. The treatment showed a QALD benefit of 1.26 [95% CI = 0.619–1.917] during the BPS, 1.90 [95% CI = 0.692–3.047] during the TPS, and 2.47 [95% CI = 0.930–4.101] during the full trial. Limitations: The generalizability of this algorithm is limited to allergy trials containing the same covariates as those present in the model. The analysis also assumes that grass and tree pollen allergy have the same relationship with EQ5D utilities, which is supported by the fact that both grass and tree pollen induce similar symptoms. Conclusions: Application of the mapping function enabled the calculation of QALDs associated with the treatment, with the caveat that data were extrapolated from grass seasonal allergy to tree seasonal allergy. The results showed a significant QALD benefit of the treatment over placebo in treatment of tree pollen-induced rhinoconjunctivitis.